Petrogenetic Study on Ultramafic Rocks from Waturapa and Surrounding Areas, South Konawe Regency, Southeast Sulawesi Province - Hasria; Masri; Muhammad Arba Azzaman; Muhamad Jerniawan (Journal of Geoscience, Engineering, Environment, and Technology, 2023)
The petrogenesis study of ultramafic igneous rocks in the South Konawe Region has been carried out by several previous researchers, however, petrogenesis of ultramafic igneous rocks in the Waturapa Region has never been carried out in detail. This study aims to determine the characteristics and petrogenesis of ultramafic igneous rocks in the Waturapa area using petrographic and geochemical analysis using the XRF method. Petrographic analysis was carried out to determine the relative abundance percentage of primary minerals in the form of olivine, clinopyroxene, orthopyroxene, and opaque minerals as well as secondary serpentine minerals which were formed later. Meanwhile, XRF geochemical analysis is used to determine the major and minor oxide content in rocks. This geochemical data is used to determine ultramafic rock types, and magma series and to interpret the tectonic setting of the research location. The results showed that the ultramafic rocks in the study area consisted of olivine websterite and lherzolite, both of which have been serpentinized which is characterized by the presence of serpentine minerals such as lizardite and chrysotile. These serpentine minerals are present as replacement minerals and fracture-filling minerals. The geochemical characteristics of the analyzed rocks showed a SiO2 content of less than 45%, high MgO content, and low K2O, TiO2, Na2O3, and P2O5 compounds. The igneous rocks in the study area are classified as ultrabasic or ultramafic rocks (peridot gabbro). Ultramafic rocks in the study area belong to the tholeiitic magma series that formed in oceanic islands or oceanic intraplate margins.